Evaluasi Pengalaman Pengguna Aplikasi Hiip Indonesia Menggunakan Metode USE Questionnaire dan Usability Testing: Studi Kasus pada PT. Hiip Inovasi Indonesia - Novariany, Rani; Kusuma, Rahma Djati (Jurnal Informatika Kesatuan, 2023)
With the rapid development of mobile applications, user experience has become crucial in ensuring success and user satisfaction. This research paper presents an evaluation of the user experience of the Hiip Indonesia application, with a focus on usability assessment and user satisfaction. The research methodology employs two main methods: the USE Questionnaire and Usability Testing. The USE Questionnaire is a validated and widely used tool for assessing user satisfaction, while Usability Testing involves observing user interactions with the application and collecting qualitative and quantitative data. The research findings indicate that the usability level of the Hiip Indonesia application falls into the "acceptable" category, with a total feasibility percentage of 73.91%. The hypothesis testing shows a significant influence on satisfaction between the variables of usefulness, ease of use, and ease of learning. However, on a partial level, only the variables of usefulness and ease of use significantly influence satisfaction. In contrast, the ease of learning variable does not have a considerable impact. Furthermore, the user experience evaluation data through task scenario testing indicates that the Hiip Indonesia application is highly effective to use, with a task completion success rate of 100% and an average task completion time of approximately 46.77 seconds. After reviewing the identified issues, recommendations for improvements to the Hiip Indonesia application have been formulated. Some of these recommendations include adding features to the "campaign" menu, adding a menu to the home screen, adding features to the "social media" menu, and adding features for chatting with administrators. Keywords: User experience, UX evaluation, USE Questionnaire, usability testing, mobile application, PT. Hiip Inovasi Indonesia.